The L2 Motivational Self System and the Instructional Willingness to Communicate in the Kuwaiti EFL Context - Alenezi, Abdullah A.; Al-Saeed, Shaima J.; Alazemi, Abdullah M. (Advances in Social Sciences Research Journal, 2021)
The study explores the relationship between Dörnyei’s (2005, 2009) L2 motivational self system (L2MSS) and the English as a foreign language (EFL) learners’ instructional willingness to communicate (IWTC). It examines specifically the impact of the three elements of the L2MSS, that is, the ideal self, ought-to self, and learning experience, on the components of the IWTC. The study used a quantitative method of data collection from a two-part questionnaire; both parts were answered by the same participants. The questionnaire was adapted and modified to fit the needs of the Arabic participants, who were 247 Kuwaiti college students. A thorough confirmatory factor analysis was implemented to validate the L2MSS and IWTC questions. The outcomes of the study revealed that each part of the questionnaire was fit to test the data, and thus the tools were authenticated for future research in an Arabic context. In addition to highlighting the significant element of the motivational self, the study looked further into the construct of the IWTC and pinpointed its most important components. The findings show that the ideal self was significantly correlated with the learning responsibility component of the IWTC. The ought-to self was found to be insignificant, and the learning experience had no factor loading and thus was excluded.